2019
DOI: 10.1097/icb.0000000000000605
|View full text |Cite
|
Sign up to set email alerts
|

Development and Progression of a Lamellar Macular Hole With Lamellar Hole–associated Epiretinal Proliferation

Abstract: Purpose: To describe evolution and progression of a lamellar macular hole (LMH) with “lamellar hole–associated epiretinal proliferation (LHEP)” using spectral-domain optical coherence tomography and fundus autofluorescence. Methods: Observational case report. Results: We report on a 63-year-old male patient demonstrating a complete history of LMH development with LHEP occurring during a follow-up period of 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…LMHs are invariably accompanied by ERM and/or epiretinal proliferation and can occasionally progress to FTMH [6,7,9,[11][12][13][14][15]. The pathogenesis of LMH progression to FTMH is poorly understood, but it is evident that the vitreous plays no role.…”
Section: Discussionmentioning
confidence: 99%
“…LMHs are invariably accompanied by ERM and/or epiretinal proliferation and can occasionally progress to FTMH [6,7,9,[11][12][13][14][15]. The pathogenesis of LMH progression to FTMH is poorly understood, but it is evident that the vitreous plays no role.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, long-term follow-up of LHEP has found not only that the size of LHEP increases on average, but that LHEP can also migrate from the retinal surface into the macular hole towards the outer retinal layers 17 . Therefore, the first possible etiologic scenario in the patient described here might be the coincident presence of a lamellar hole with associated epiretinal proliferation and PEVAC, which gained connection to LHEP tissue because of long-standing disease and LHEP migration towards the vascular lesion.…”
Section: Discussionmentioning
confidence: 99%
“…In LMHs epiretinal proliferation is seen around/surrounding the edges of the defect and moulds with the inner retinal anatomy [7]. Both ERM and epiretinal proliferation can co-exist manifesting mixed features [4,7,9,10,12].…”
Section: Natural History and Historical Reviewmentioning
confidence: 99%
“…During the mean follow-up period of 26 months only one eye progressed to FTMH but it is not specified from which group; otherwise functionally & morphologically the LHEP group fared worse. Compera et al [ 12 ] reported a case of LMH with LHEP (epiretinal proliferation) that progressed to FTMH. dell’Omo et al [ 9 ] analysed 84 eyes with LMH, of which 43 had standard ERM alone (likely similar to ERM foveoschisis), 11 had LHEP alone (likely similar to true LMH) and 30 had both.…”
Section: Natural History and Historical Reviewmentioning
confidence: 99%
See 1 more Smart Citation